In the motions a cathartic release of anxiety through drawing and painting - Lirio, Francheska Rae Z.; Feleo, Roberto; Sta Ana, Mary Catherine (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
My thesis is a visual representation of my cathartic release of anxiety and intense emotions. My work features the spontaneous, gestural, mark-making manner characteristic of the abstract expressionists with the use of varied mediums on different found surfaces as ground. The process is cathartic, a form of art therapy. The resulting work, comprised of differing sized works, is presented as a collaged piece on a 12 feet by 4 feet frame, wall-bound. The work aims to ease my social anxiety through the cathartic process, and raise awareness about this condition.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaf 21
Keywords: Anxiety; Social anxiety disorder; Catharsis; Therapeutics in art